PERAN PENDIDIKAN BAHASA ARAB TERHADAP KEMAMPUAN BERBAHASA SISWA: KAJIAN KEPUSTAKAAN - Amalia, Filsa; Nuraeni, Indri; Syahra, Adila; Agustina; M. Haikal; Andika, Caca; Kamus (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Arabic language education plays an important role in improving students’ language skills; however, the learning process in Indonesia still faces several challenges, including limited learning methods, low student motivation, and inadequate opportunities for language practice. These issues affect students’ ability to master language skills effectively. Therefore, this study aims to analyze the role of Arabic language education in improving students’ language skills through language competency development, vocabulary mastery, and factors influencing the learning process. This study employed a qualitative approach using a library research method. Data were collected and analyzed from 17 journal articles published between 2016–2025 that were relevant to the research topic. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. Thefindings indicate that Arabic language education contributes significantly to improving students’ language skills through the development of four language competencies, namely listening, speaking, reading, and writing skills. Furthermore, vocabulary mastery (mufradat) was found to have a positive influence on students’ language abilities. Supporting factors such as innovative teaching methods, teacher competence, and a conducive learning environment also contribute to enhancing students’ language development. Therefore, Arabic language education should be designed effectively and student-centered to optimize students’ language skills.